Children’s Informant Judgments and Recall of Valenced Facts at a Science Center - Marble, Kimberly E.; Caporaso, Jessica S.; Bettencourt, Kathleen M.; Boseovski, Janet J.; Pathman, Thanujeni; Marcovitch, Stuart; Scales, Margaret L. (Frontiers in Psychology, 2021)
In laboratory-based research, children recognize who is an expert and demonstrate an interest in learning from that person. However, children prefer positive information in the moment and sometimes prioritize positivity over expertise. To what extent do these social judgments (e.g., a preference for positivity) relate to information that children remember? We investigated the relation between these judgments and memory at a local science center to better understand children’s learning outcomes in naturalistic settings. We examined the extent to which 4- to 8-year-olds accepted facts about an unfamiliar animal from a zookeeper informant (i.e., expert) and a maternal figure (i.e., non-expert) when these facts were positive, negative, or neutral. Children endorsed positive information as correct, regardless of expertise, but demonstrated the strongest memory for neutral information. We discuss the implications of this dissociation for learning outcomes in naturalistic contexts as well as theoretical frameworks regarding children’s learning from others.